Sustainable Education for Refugee Children: A Quasi-Experimental Study - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Hassan, Masmunaa; Win, Kyu Kyu; Sutrisno, Resti Yulianti (Proceedings Series on Health & Medical Sciences, 2025)
Refugee children are unable to access formal education like public schools due to their status with no citizenship. According to sustainable development goals (SGDs), everyone should have equal access to formal education. Objective: This study aimed to evaluate the effectiveness of sustainable education programmes for refugee children. Method: An educational programme was provided to refugee children by using a quasi-experimental approach with 27 refugee children for a period of 1 year. The program consisted of teaching sessions in four subjects: Malay language, mathematics, Islamic lessons, and science. Pre- and post-program assessments were used to measure changes in the children’s learning outcomes. Significant improvements were observed across all subjects. Malay language competency increased, with 36% of younger children and 44% of older children able to vocalize more than five alphabets post-program. In mathematics, all children could count from 1-10 post-program, with 80% mastering basic arithmetic. Islamic knowledge also improved, with 90% of children able to recite Surah Al-Fatihah correctly. In science, 75% of children could identify body parts accurately. The results indicate that structured educational interventions can significantly enhance the learning outcomes of refugee children. Future programs should focus on sustaining these efforts through partnerships and improving teacher training.